American 'committed' drama in Slovene theatres - Igor Maver (Acta Neophilologica, 1994)
The purpose of this study is essentially to demonstrate that the delayed stagings of American 'committed' plays, written in the thirties and produced in Slovene theatres immediately after World War Two in the late forties and fifties, were often miscontextualized and partly misinterpreted by the literary critics of the period. This was only in the early post-war years largely due to the need to serve the then ruling ideology and to comply with the criteria of Marxist aesthetisc, especially that of a radical social criticism. However, the later stagings particularly of Arthur Miller's and also Tennessee Williams's plays, did not see the same phenomenon, for it was they that assured the popularity of the American post-war drama on Slovene stages and, even more importantly, helped Slovene theatre to come off age in the sixties.